Endocrine response to resistance training in children - Falk, B.; Eliakim, A. (Pediatric Exercise Science, 2014)
The aim of this manuscript is to summarize the available literature on the hormonal response to resistance exercise and training in youth. The discussion below addresses only those hormones which have been examined in relation to resistance exercise or resistance training in children and adolescents, while many other hormones, growth factors, and myokines may be of interest, the discussion will focus only on those humoral agents for which information is available on youth. In view of the scant available literature specific to this topic, some inference will also be made to young athletes who train in sports which are characterized by a large component of resistance or power training (eg, gymnastics, martial arts). For each hormone, or hormonal axis, chronic and acute effects are examined separately, and a comparison is made with adult literature (see summary Tables 3 and 4). Finally, the rationale and need for future studies is examined.